Forefront of Na+/Ca2+ Exchanger Studies: Role of Na+/Ca2+ Exchanger - Lessons From Knockout Mice - Issei Komuro; Masashi Ohtsuka (Elsevier, 2004)
We used Na+/Ca2+ exchanger (NCX) knockout mice to evaluate the effects of NCX in cardiac function and the infarct size after ischemia/reperfusion injury. The contractile function in NCX KO mice hearts was significantly better than that in wild type (WT) mouse hearts after ischemia/reperfusion and the infracted size was significantly smaller in NCX KO mice hearts compared with that in WT mice hearts. NCX is critically involved in the development of ischemia/reperfusion-induced myocardial injury, and therefore the inhibition of NCX function may contribute to cardioprotection against ischemia/reperfusion injury. Keywords:: Na+/Ca2+ exchanger (NCX), knockout mouse, heart, ischemia/reperfusion injury